2015
DOI: 10.1080/19425120.2015.1074968
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Delayed Mortality from Barotrauma Impairment in Discarded Red Snapper Using Acoustic Telemetry

Abstract: Red Snapper Lutjanus campechanus is the most economically important reef fish in the Gulf of Mexico, and despite being intensively managed, the stock remains overfished. These fish are susceptible to pressure‐related injuries (i.e., barotrauma) during fishing that compromise survival after catch and release. Barotrauma‐afflicted fish may not only experience immediate mortality but also delayed mortality after returning to depth. This variability and unknown fate leads to uncertainty in stock assessment models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 48 publications
2
71
0
Order By: Relevance
“…() and Curtis et al. () found that venting was as effective as recompression at increasing rates of postrelease survival among telemetered Red Snapper. Pulver () found for several species of deepwater groupers (family Serranidae) that the predicted probability of survival increased by at least 50% when using venting compared with releasing groupers untreated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Curtis et al. () found that venting was as effective as recompression at increasing rates of postrelease survival among telemetered Red Snapper. Pulver () found for several species of deepwater groupers (family Serranidae) that the predicted probability of survival increased by at least 50% when using venting compared with releasing groupers untreated.…”
Section: Discussionmentioning
confidence: 99%
“…; Curtis et al. ), and Snowy Grouper Hyporthodus niveatus (Runde and Buckel ). Thus, the finding that recompression increases survival rates of Black Sea Bass reeled from relatively high pressures (approximately 5 atm) is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of fish descending gear and venting tools increased the survival of released Red Snapper by 3.0 and 1.9 times, respectively (Curtis et al. ).…”
mentioning
confidence: 99%
“…Were predation explicitly accounted for (e.g., through tagging studies), increases to the estimates of fishing‐related mortality would be likely (Curtis et al. ) and the inferred effect of the recreational fishery would likewise increase. Given these unresolved issues, we echo the recommendation by Campbell et al.…”
Section: Discussionmentioning
confidence: 99%